Agricultural Technology Information Centre (ATIC): Farmers’ Perception - M. A. Dar , Safeer Alam , Jasvinder Kaur , D. Ram , Shafiqul Islam; A. M. Tantray (Indian Journal of Extension Education, 2014)
The present study was conducted for impact assessment of ATIC by measuring the level of satisfaction of the farmers visiting the ATIC. Data from 59 farmers were collected who visited and registered at ATIC, SKUAST-Kashmir during last four years (2006-2010). The selection of farmers was made by random sampling technique. The data collected with the help of pre-structured interview schedule and analyzed to assess the level of satisfaction. ATIC products, services and information were rated very important and useful, but the respondents were dissatisfied with the availability of products, services and informations provided to the farming community. It is, thus, recommended that there should be some improvement in the availability of quality products and other services and information to be provided to the farmers.